Sialylation inhibition improves macrophage mediated tumor cell phagocytosis of breast cancer cells triggered by therapeutic antibodies of different isotypes - Lustig, Marta; Hahn, Christoph; Leangen Herigstad, Marie; Andersen, Jan Terje; Leusen, Jeanette H. W.; Burger, Renate; Valerius, Thomas (Frontiers in Oncology, 2024)
Tumor cell phagocytosis by macrophages is considered a relevant mechanism of action for many therapeutic IgG antibodies. However, tumor cells employ several mechanisms to evade immune recognition, including hypersialylation. Here, we describe how reduction of sialic acid exposure on tumor cells promotes antibody-dependent tumor cell phagocytosis (ADCP) by macrophages. Incubation with the sialyltransferase inhibitor (STi) P-3Fax-Neu5Ac reduced sialylation on two breast cancer cell lines, rendering these cells more susceptible to macrophage mediated phagocytosis by EGFR or HER2 antibodies. This was observed with not only IgG1 and IgG2 antibodies but also IgA2 variants. These results show that inhibiting sialic acid exposure triggers enhanced tumor cell phagocytosis by macrophages irrespective of the antibody isotype and the tumor target antigen. Investigating the underlying mechanisms of enhanced ADCP, we observed reduced binding of soluble sialic acid-binding immunoglobulin-like lectins (Siglec)-7 and Siglec-9 to tumor cells after sialylation inhibition. However, Fc silent blocking antibodies against Siglec-7 or Siglec-9, or their combination, only marginally improved ADCP. Our results further promote the concept of cancer hypersialylation as immune escape mechanism, which could serve as target to improve tumor immunotherapy with monoclonal antibodies.